Reliability and discriminant validity of ataxia rating scales in early onset ataxia. (21st October 2016) - Brandsma, Rick; Lawerman, Tjitske F; Kuiper, Marieke J; Lunsing, Roelineke J; Burger, Huibert; Sival, Deborah A
Abstract : Aim: To determine whether ataxia rating scales are reliable disease biomarkers for early onset ataxia (EOA). Method: In 40 patients clinically identified with EOA (28 males, 12 females; mean age 15y 3mo [range 5–34y]), we determined interobserver and intraobserver agreement (interclass correlation coefficient [ICC]) and discriminant validity of ataxia rating scales (International Cooperative Ataxia Rating Scale [ICARS], Scale for Assessment and Rating of Ataxia [SARA], and Brief Ataxia Rating Scale [BARS]). Three paediatric neurologists independently scored ICARS, SARA and BARS performances recorded on video, and also phenotyped the primary and secondary movement disorder features. When ataxia was the primary movement disorder feature, we assigned patients to the subgroup 'EOA with core ataxia' ( n =26). When ataxia concurred with other prevailing movement disorders (such as dystonia, myoclonus, and chorea), we assigned patients to the subgroup 'EOA with comorbid ataxia' ( n =12). Results: ICC values were similar in both EOA subgroups of 'core' and 'comorbid' ataxia (0.92–0.99; ICARS, SARA, and BARS). Independent of the phenotype, the severity of the prevailing movement disorder predicted the ataxia rating scale scores ( β =0.83–0.88; p <0.05). Interpretation: In patients with EOA, the reliability of ataxia rating scales is high. However, the discriminative validity for 'ataxia' is low. For adequate interpretation of ataxia rating scale scores, application in uniform movement disorder phenotypes is essential. What this paper adds: Ataxia rating scales (ARS) are reliable in assessing early onset ataxia (EOA). Discriminant validity of ARS is low. ARS scores should be interpreted in homogeneous EOA phenotypes. This article is commented on by Saute and Jardim on pages350–351 of this issue. Video Podcast:https://youtu.be/F6FZgg0yPdE